2022
DOI: 10.1038/s41598-022-06915-z
|View full text |Cite
|
Sign up to set email alerts
|

Ether anesthetics prevents touch-induced trigger hair calcium-electrical signals excite the Venus flytrap

Abstract: Plants do not have neurons but operate transmembrane ion channels and can get electrical excited by physical and chemical clues. Among them the Venus flytrap is characterized by its peculiar hapto-electric signaling. When insects collide with trigger hairs emerging the trap inner surface, the mechanical stimulus within the mechanosensory organ is translated into a calcium signal and an action potential (AP). Here we asked how the Ca2+ wave and AP is initiated in the trigger hair and how it is feed into systemi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
6

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 40 publications
0
21
0
6
Order By: Relevance
“…Significantly upregulated GO-MF categories of “calcium ion binding” and “calmodulin binding” are in accordance with the role of Ca 2+ in signaling during anesthesia ( Figure 2F ). This finding is partially interesting in the view of recent studies showing that diethyl ether blocked wound-induced glutamate-dependent Ca 2+ transient and systemic response mediated by GLR channels in A. thaliana ( Jakšová et al, 2021 ) and D. muscipula ( Scherzer et al, 2022 ). Different kinetics of these [Ca 2+ ] cyt responses suggest participation of two different Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Significantly upregulated GO-MF categories of “calcium ion binding” and “calmodulin binding” are in accordance with the role of Ca 2+ in signaling during anesthesia ( Figure 2F ). This finding is partially interesting in the view of recent studies showing that diethyl ether blocked wound-induced glutamate-dependent Ca 2+ transient and systemic response mediated by GLR channels in A. thaliana ( Jakšová et al, 2021 ) and D. muscipula ( Scherzer et al, 2022 ). Different kinetics of these [Ca 2+ ] cyt responses suggest participation of two different Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 65%
“…Recent studies showed that the anesthetic diethyl ether strongly suppresses the sensing of different stimuli in plants (e.g., light, touch, or wounding, Milne and Beamish, 1999 ; De Luccia, 2012 ; Yokawa et al, 2018 ; Pavlovič et al, 2020 ; Böhm and Scherzer, 2021 ; Jakšová et al, 2021 ; Scherzer et al, 2022 ). Here we show it concomitantly triggers also a strong cellular response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 2: Phylogenetic distribution, membrane localization and functions of MSL, OSCA, MCA and Piezo channels. MSLs: Redox homeostasis and Membrane potential dissipation[101], Osmoprotection[102] [54],[103], Pollen rehydration[59], Root mechanosensitivity[31], Modulation of the susceptibility to Pseudomonas[58] [104], Long distance wound-induced electrical and Ca 2+ signaling[63],Cell swelling[60], Amplification of oscillatory signals[34], Prey recognition[65] [64]; OSCAs: Adaptation to osmotic stress[91], Candidate to drought stress tolerance[90], Candidate to abiotic stress tolerance[92], Immunity based stomatal closure [89], Osmotic signaling in guard cells and root cells[85]; MCAs: Gravity sensing[72], Osmotic signaling[74], Plant architecture[75],[76],[105], Penetration of the root[73] [71]; Piezos: Root apex mechanosensing[83]and root Ca 2+ signaling[83],[84], Immune response to virus[82], Regulation of vacuole shape[78] …”
mentioning
confidence: 99%